The Impact of Tax Incentive on Increase Foreign Direct Investment - Kusumaningtyas, Reza Octavia; Kalimanzila, James (Lembaga Contrarius Indonesia, 2023)
This study examines and describes the effect of applying tax incentives through the tax allowance policy on the growth of direct investment in Indonesia. Legal research is the method of inquiry employed. Legal issues are analyzed using doctrinal research to draw logical conclusions. Legal research enhances the quality of research projects. The application of tax incentives has resulted in an increase in total investment of 187%, and the number of recipients of tax incentives has increased from 69 to 71 and continues to grow annually. Additionally, the incentives have a positive effect on other nations. Several obstacles and barriers exist in its implementation, including inefficiency in the government system, political relations with businesses, and economic stability.